The effects of laryngeal mask versus endotracheal tube on atelectasis after general anesthesia induction assessed by lung ultrasound: A randomized controlled trial - Liu, Bin; Wang, Yaxin; Li, Ling; Xiong, Wei; Feng, Yifan; Liu, Yan; Jin, Xu (Journal of clinical anesthesia, 2024)
This study aims to evaluate the impact of Supreme™ laryngeal masks versus endotracheal tubes on atelectasis during general anesthesia using lung ultrasound (LUS), and provide evidence for respiratory management. A single-center, double-blind, randomized controlled trial was conducted. The study was conducted in both the operating room and the post-anesthesia care unit, with follow-up assessments performed in the ward. Enrollment included 180 cases undergoing non-laparoscopic surgeries in gynecology, urology, and orthopedic limb surgeries. Patients were randomly assigned 1:1 to the endotracheal intubation or laryngeal mask group. LUS scores were recorded across 12 lung regions at baseline, 15 min after airway establishment, at the end of surgery, and 30 min following airway removal. Outcome measures encompassed the oxygenation index, dynamic lung compliance, incidence of postoperative pulmonary complications, throat pain, and other postoperative complications assessed at 24 and 48 h postoperatively. The primary outcome focused on the LUS score in all 12 lung regions at 15 min after airway establishment. Intention-to-treat analysis of 177 subjects revealed endotracheal intubation led to significantly higher LUS scores at 15 min {P < 0.001, mean difference 4.15 ± 0.60, 95% CI [2.97, 5.33]}, end of surgery (P < 0.001, mean difference 3.37 ± 0.68, 95% CI [2.02, 4.72]), and 30 min post-removal (P < 0.001, mean difference 2.63 ± 0.48, 95% CI [1.68, 3.58]). No major complications occurred in the two groups. Compared to endotracheal intubation, laryngeal masks effectively reduce atelectasis formation and progression in gynecological, urological non-laparoscopic, and orthopedic limb surgeries. However, caution is warranted when generalizing these findings to surgeries with a higher risk of laryngeal mask leakage or obese patients. Additionally, the efficacy of laryngeal masks in reducing postoperative atelectasis remains uncertain when comprehensive monitoring of muscle relaxation and reversal therapy is employed. •Atelectasis can develop during general anesthesia and persist post-surgery.•Laryngeal masks effectively reduce lung ultrasound scores and improve oxygenation during general anesthesia compared to endotracheal tubes.•The results are applicable to non-laparoscopic surgeries and healthy individuals without underlying pulmonary conditions.